2022
DOI: 10.1186/s12873-022-00699-1
|View full text |Cite
|
Sign up to set email alerts
|

Paramedic management of back pain: a scoping review

Abstract: Background Research examining paramedic care of back pain is limited. Objective To describe ambulance service use and usual paramedic care for back pain, the effectiveness and safety of paramedic care of back pain, and the characteristics of people with back pain who seek care from paramedics. Methods We included published peer-reviewed studies of people with back pain who received any type of paramedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Of note however is that the same review reported that up to one third of these ED transfers were avoidable. 27 Our findings of increasing LBP ED presentations and greater serious pathology in the older age group highlight the need for further research into changing ambulance usage and the resultant hospital sequelae of ambulance transfers for LBP to the ED.…”
Section: Discussionmentioning
confidence: 75%
“…Of note however is that the same review reported that up to one third of these ED transfers were avoidable. 27 Our findings of increasing LBP ED presentations and greater serious pathology in the older age group highlight the need for further research into changing ambulance usage and the resultant hospital sequelae of ambulance transfers for LBP to the ED.…”
Section: Discussionmentioning
confidence: 75%
“…Transcutaneous electrical nerve stimulation (TENS) is a physical therapy method commonly used in the treatment of pain (Vance et al, 2012;Santuzzi et al, 2013). It is used as a technique with successful results in the reduction of fibromyalgia (Dailey et al, 2022), primary dysmenorrhea pain (Arik et al, 2022), shoulder pain (Bilek et al, 2021), back pain (Vella et al, 2022) and chronic cancer pain (Katta et al, 2022). TENS enhances local inhibitory control and is indicated in focal neuropathic pain (NP) (Guastella et al, 2008).…”
Section: Discussionmentioning
confidence: 99%